Effects of post‐silking drought stress degree on grain yield and quality of waxy maize. (21st October 2022) - Guo, Jian; Qu, Lingling; Wang, Longfei; Lu, Weiping; Lu, Dalei
Abstract: BACKGROUND: Drought stress (DS) induced by post‐silking have a major impact on the yield and quality of maize. In this study, the effects of different degrees of DS after pollination on grain filling, starch and protein metabolism, and functional properties were investigated using two waxy maize cultivars as materials. The levels of DS that were investigated were 'mild water stress' (WS1), 'moderate water stressed' (WS2), and 'severe waterstressed' (WS3). RESULTS: Drought stress decreased grain fresh weight, dry weight, and moisture content in both cultivars during grain filling, and reduced kernel number, kernel weight, and grain yield at maturity. The effect on grain development and yield formation gradually increased with drought aggravation. The water stress (WS) treatment downregulated the enzymatic activities related to starch biosynthesis during grain‐filling process, accompanied by a decrease in soluble sugar and starch deposition. The WS treatment increased the enzymatic activities involved in protein synthesis during grain‐filling process, thereby increasing the protein content of grains. On average, WS2 and WS3 treatments reduced the pasting viscosities and increased the gelatinization temperatures of grains, with WS3 having the greatest effect. However, the changes of setback viscosity, gelatinization enthalpy, retrogradation enthalpy, and retrogradation percentage under WS treatment were inconsistent in both cultivars. Pearson correlation analysis showed that starch content was negatively correlated with gelatinization temperatures and positively correlated with pasting viscosities in both cultivars. However, grain pasting  and gelatinization properties have opposite correlations with protein content and starch content. CONCLUSIONS: These findings suggest that post‐silking DS regulated the grain‐filling process and starch and protein biosynthesis, which influenced grain yield and quality. © 2022 Society of Chemical Industry.